Observation of ultrasharp metamagnetic jumps in polycrystalline Er2Cu2O5. (7th February 2017) - Banerjee, A; Sannigrahi, J; Giri, S; Majumdar, S
Abstract: The observation of ultrasharp metamagnetic jumps in the field variation of magnetization ( M versus H ) data for the highly insulating metal oxide Er2 Cu2 O5 is investigated. The compound orders antiferromagnetically below about T N 1   =  28 K and shows conventional 'not-so-sharp' metamagnetism around 13 kOe on the field-increasing leg in the polycrystalline sample. The uniqueness of the ultrasharp jumps in Er2 Cu2 O5 resides in the fact that they are only observed in the field-decreasing segment of the magnetization curve. We observe that the jumps are affected by the sweep rate of the magnetic field, similarly to several other systems that show such ultrasharp jumps. Er2 Cu2 O5 shows a considerable amount of thermo-remanent magnetization when it is cooled in a field that is higher than the critical field of 13 kOe. Our analysis indicates that above 13 kOe the system remains phase separated, with the coexistence of antiferromagnetic and field-induced ferromagnetic-like phases. The jumps in the return leg occur because of the shear-dominated martensitic-like phase transition of the ferromagnetic-like phase to an antiferromagnetic phase, and interfacial strain plays a major role in the observed jumps.